Investigation of The Correlation between Metacognition Levels and Ruminative Thought Forms of Sports Sciences Faculty Students - kara, N. Şeyma (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this research is to investigate the correlation between the metacognition levels of the students of the faculty of sports sciences and their ruminative thought styles. Method: The research is carried out using the correlational survey model. The universe of the research consists of sports science students studying at Hatay Mustafa Kemal University, Faculty of Sports Sciences, Department of Coaching, Physical Education and Sports Teaching, Recreation and Sports Management. The sample of the study, on the other hand, is a total of 287 sports science students, 131 female and 156 male, selected by convenience sampling. Pearson correlation and regression techniques are used in the analysis of the data. Results: As a result of the research, it is determined that there is a moderately significant positive correlation between metacognitive awareness scores and ruminative thought style scores. In addition, it is determined that metacognitive awareness is a significant predictor of ruminative thought. Conclusion: Based on the results of the research, excessive control of cognitions may cause repetitive thoughts.